A representação do imigrante judeu na literatura do Rio Grande do Sul : Cágada e O exército de um homen só - Rodrigues, Gláucia Elisa Zinani (2019)
This study deals with the representation of the Jewish immigrant in the contemporary literature of Rio Grande do Sul, with the cutout in the work of Gladstone Osório Mársico (1927-1976) and Moacyr Scliar (1937-2011). The presence of Jewish immigrants in the state dates from the beginning of the Twentieth century, with the founding of the Quatro Irmãos colony that also corresponded to the areas of the Baronesa Clara and Barão Hirsch villages, in the rural area in 1909, in the northern region of Rio Grande do Sul and the establishment of a large contingent of immigrants in the capital, located in the neighborhood Bom Fim, around 1914 linked to trade and craft professions. They distinguished themselves from other immigrants mainly because of religion. The objective is to analyze the representation of the Jewish immigrant in the literature, opting for the works Turtle (or the history of a municipality by step of), published in 1974, with the setting of the four brothers farm in Erechim; And the work the One man's army, from Scliar, published in 1973, set in the neighborhood Bom Fim, in Porto Alegre. Thus, the proposal is justified by analyzing the presence of the Jew in the literature, precisely because of its representation in a marginal way, sometimes through satire, sometimes by irony. The study, in theoretical methodological terms, dialogues with Cultural history and is located on the border between literature and history. The intersection of sources includes bibliographic review, documents on immigration by oral and literary sources. Based on the collected data, both authors, Scliar of Jewish origin, and Mársico, lawyer of the Jewish Colonization Association (ICA), were eyewitnesses of the Jewish presence in the state, merging in their literary works historical knowledge, experiences Social and cultural backgrounds. Soon, their characters move in urban and rural space, carry with them their culture, their religiosity, their knowledge and doing, living their daily lives. The Jewish immigrant, in immigration spaces, presents a homogeneous external ethnic identity, superimposed on internal heterogeneity, occupying mainly urban spaces, dedicating itself to activities of craft and trade, representation this reproduced Also in the literature, and critically, in relation to the colonization of the colony of four brothers, as a project that was not successful but, reached the objectives of assisting Jewish immigrants victims of discrimination in eastern European countries.